2018
DOI: 10.18621/eurj.353985
|View full text |Cite
|
Sign up to set email alerts
|

Nausea and vomiting in pregnant adolescents: impact on health-related quality of life

Abstract: Objectives:To determine the impact of the presence and severity of nause and vomiting in pregnancy (NVP) on health-related quality of life in pregnant adolescents. Methods: Two hundred and fifty adolescent pregnant women were included in this study. The Rhodes test was performed to determine the severity of nausea and vomiting, and the self-reported 36-Item Short Form Survey (SF-36) Scale was administered. The study was divided into four groups according to nausea severity (no, mild, moderate, severe) groups a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 30 publications
2
7
0
Order By: Relevance
“…NVP affects health physically and mentally 46 . Research shows that NVP or HG decreases physical performance, prevents activities of daily living, causes stress and depression, and reduces QoL 10‐12,32,46‐49 . In this study, CAM users had lower “emotional role” scores than nonusers ( p = 0.038), indicating that pregnant women with low “emotional role” QoL use CAM more.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…NVP affects health physically and mentally 46 . Research shows that NVP or HG decreases physical performance, prevents activities of daily living, causes stress and depression, and reduces QoL 10‐12,32,46‐49 . In this study, CAM users had lower “emotional role” scores than nonusers ( p = 0.038), indicating that pregnant women with low “emotional role” QoL use CAM more.…”
Section: Discussionmentioning
confidence: 52%
“…Lacasse et al 11 reported a negative correlation between the severity of NVP symptoms and QoL in pregnant women ( n = 367). Yılmaz et al 10 found that the higher the severity of NVP symptoms, the lower the mean SF‐36 QoL scores. Munch et al 12 reported that pregnant women with HG have lower QoL scores than those without HG.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the first study to analyze the quality of life of women with pre-eclampsia who undergoing antenatal care and it indicated that the group receiving antenatal care had a good quality of life. The previous research on the relationship between quality of life and severity of pre-eclampsia that required treatment indicated that quality of life was negatively correlated with severity [10], [11], [12], [13]. Based on this logic, we can deduce that only women with severe pre-eclampsia have a lower quality of life than mild pre-eclampsia.…”
Section: Discussionmentioning
confidence: 72%
“…Women who experience pregnancy between the ages of 18 and 35 years are less likely to experience pregnancy problems, and when faced with pregnancy problems, they will be better able to adapt. [ 32 ] Young, educated, and working mothers, due to their better socioeconomic status, are likely to have a greater and better understanding of the importance of their health and their impact on fetal health and more on their appearance and weight control and body mass index. [ 12 33 ]…”
Section: Discussionmentioning
confidence: 99%